2020
DOI: 10.3389/fonc.2020.01023
|View full text |Cite
|
Sign up to set email alerts
|

Characterizations of Cancer Gene Mutations in Chinese Metastatic Breast Cancer Patients

Abstract: Background: Breast cancer (BC) is a type of disease with high heterogeneity. Molecular profiling, by revealing the intrinsic nature of its various subtypes, has extensively improved the therapeutic management of BC patients. However, the genomic mutation landscape of Chinese metastatic BC has not been fully explored. Methods: Matched plasma and mononuclear cells from 290 Chinese women with metastatic BC were sequenced using either of the two commercially-available panels consisting of 520 cancer-related and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 42 publications
3
16
0
1
Order By: Relevance
“… 26 Another recent study on cfDNA molecular profiling in Chinese patients with MBC reported a TP53 mutation rate of 64.1% compared with 52% in Caucasian patients. 27 , 28 These discrepancies could reflect differences between patient ethnicities, such as in the median age of breast cancer patients with TP53 mutations in our study of 48 years compared with 55.2 years in Caucasians. 29 …”
Section: Discussionmentioning
confidence: 65%
“… 26 Another recent study on cfDNA molecular profiling in Chinese patients with MBC reported a TP53 mutation rate of 64.1% compared with 52% in Caucasian patients. 27 , 28 These discrepancies could reflect differences between patient ethnicities, such as in the median age of breast cancer patients with TP53 mutations in our study of 48 years compared with 55.2 years in Caucasians. 29 …”
Section: Discussionmentioning
confidence: 65%
“…In addition, there is evidence that genomic changes are obtained in the process of cancer metastasis and progression and the genomic pattern of early cancers cannot represent lethal cancers ( 32 36 ). Recently, there have been subsequent reports on the genomic landscape of mBC ( 16 18 ). However, the molecular mechanism for LM remains an area that has not yet been fully developed ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another example is that the interaction between chemokine receptors on tumor cell membranes and chemokines in the microenvironment, such as CCL2 ( 10 , 11 ) and CXCR4-CXCL12/SDF-1 ( 12 14 ), plays important roles in LM. Moreover, with the rapid development of sequencing technology in the recent years, a large number of early BC gene maps have been reported, along with several reports on the overall mutation characteristics of mBC ( 15 18 ). However, the genetic landscape related to LM alone has not yet been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…PTEN is a multifunctional tumor suppressor gene, which is mutated in large number of cancers at different frequency. PTEN alterations are more frequent in glioblastoma (30%-60%) [22,23], breast cancer(11%-15%) [24,25], prostate cancer (17%-21%) [26,27]. PTEN mutation is thought to be an early step in the development and progression of EC patients [28,29].…”
Section: Discussionmentioning
confidence: 99%